Educação ambiental: o lixo no ambiente escolar, uma proposta pedagógica para o novo ensino médio em escola pública - Sousa, Ana Francisca Machado de (2024)
The focus of this study was Environmental Education, within the area of ​​Natural Sciences and more specifically in the discipline of Biology. The main objective was to analyze the relevance of an educational product in the form of a Didactic Sequence, which addresses the problematization of knowledge and focuses on the management of school waste. The methodology used was qualitative, employing the action research model, which seeks to understand and interpret human experiences, considering the totality of a phenomenon. The approach to the problem is based on narrative information, stories and explanations. For data collection, observation of the participants and the application of questionnaires were used, without the adoption of a structured method for the analysis of qualitative results. The Educational Product through a Didactic Sequence. The research and the execution of the study sought to answer the central question: "What is the impact of an Educational Product with DS, on "waste" for changing significant habits and attitudes among students in the school environment?" Students express a positive and conscious understanding of the importance of collaboration in preserving the environment, demonstrating prior knowledge about recycling, material decomposition time and the relationship between environmental cleanliness and personal health. Reflecting on this topic is crucial to fostering changes in habits and critical interventions, starting at school and extending to homes and the community. The application of the Teaching Sequence resulted in several benefits, such as the development of socio-emotional skills, improved language skills, and encouragement of student leadership. The responses reflect an awareness of the interdependence between individual actions and collective well-being, highlighting the importance of approaches that encourage sustainable behaviors. In general, students are receptive to environmental responsibility and ready to actively contribute to preserving the environment. The Educational Product with the Teaching Sequence on the Environment has proven to be effective in promoting Environmental Education in schools, addressing the concept of "trash" in a broad and instructive way, offering accessible language and practical proposals to reduce the impact of human activities on the environment. Link to access the educational product on the EduCapes portal: http://educapes.capes.gov.br/handle/capes/920973.